Молодой Эйхенбаум и Молодой Толстой: Литература как оформление опыта жизни - Evgeny Dobrenko (Avtobiografija, 2013)
The article analyses Boris Eikhenbaum’s studies related to Mikhail Lermontov and Lev Tolstoy. It demonstrates that Eikhenbaum’s works related to these authors contained many polemical touches with various critics of the 1920s who aspired to appropriate Russian realist mode of writing for the construction of a new type of artistic expression. It suggests that Eikhenbaum’s interest in the literary devices found in the works of Tolstoy was inseparable from the scholar’s concerns about the interaction between life experiences and literary processes in the light of Formalist theories.